(untitled) (Homoeopathy for All, 2025)
Osteoporosis is a metabolic bone disorder characterized by reduced bone mass and deterioration of bone microarchitecture, leading to increased bone fragility and a higher risk of fractures. Known as the "silent thief," osteoporosis often progresses without symptoms until a fracture occurs. The disease primarily affects the elderly, especially postmenopausal women, due to hormonal changes that accelerate bone loss. This article delves into with osteoporotic fractures is projected to rise substantially with aging populations. In India, osteoporosis affects an estimated 50 million people, predominantly postmenopausal women. Studies suggest that Indian women lose bone density earlier, often beginning in their 30s, due to factors such as nutritional deficiencies, low calcium intake, and vitamin D deficiency caused by limited sun exposure and dietary patterns. Urbanization, sedentary lifestyles, and poor awareness of bone health further exacerbate the issue. Hip fracture rates in India are expected to increase significantly in the coming decades due to demographic changes and increased life expectancy, making osteoporosis a growing concern for healthcare systems in the country.